THE YOUTS’S ACTİVİTY DEVELOPMENT AND THEİR EDUCATİON İN HOLY QUR’AN - İlhami GÜNAY (Fırat University, 2019)
Humanbeing is honered by being appointed as chalif of the world and was created together with the required instruments to be able to render the the duty he assumed. Allah, the Almighty, have informed the the humanbeing his/her duties to be fulfilled during the lifetime from the mother's womb to the tomb and guided him/her through the devine books and the applications of the prophets. From the birth to his/her age to handle itself, He has given his/her custody to his/her parents for a healthy development and maintanence. After puberty, He has made him/herself responsible for maintaining physical and mental health of his/her own and of those under his/her responsibility according to the certain principles.